Tradycyjne systemy premiowe a zarządzanie przez wartość (ZPW) - Czarnecki, Maciej (Widespread Incentive Systems in the Context of the VBM, 2008)
Widespread Incentive Systems are usually ineffective in the context of the Value Based Management (VBM). It is recommended by VBM propagators to design and implement incentive systems which stimulate all employees to create value and, in this way, stimulate corporate value creation. It was the author's aim to briefly introduce the ineffectiveness of commonly used incentive tools in the context of the VBM. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 36-46